Comparison of the effects of monounsaturated fatty acids and polyunsaturated fatty acids on the lipotoxicity of islets - Liu, Wen; Zhu, Min; Liu, Jingyi; Su, Shan; Zeng, Xin; Fu, Fudong; Lu, Yanrong; Rao, Zhiyong; Chen, Younan (Frontiers in Endocrinology, 2024)
Background: Monounsaturated fatty acids (MUFAs) and polyunsaturated fatty acids (PUFAs) have been reported to combat saturated fatty acid (SFA)-induced cellular damage, however, their clinical effects on patients with metabolic diseases such as diabetes and hyperlipidemia are still controversial.Since comparative studies of the effects of these two types of unsaturated fatty acids (UFAs) are still limited. In this study, we aimed to compare the protective effects of various UFAs on pancreatic islets under the stress of SFA-induced metabolic disorder and lipotoxicity.Methods: Rat insulinoma cell line INS-1E were treated with palmitic acid (PA) with or without UFAs including eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), arachidonic acid (AA), and oleic acid (OA) to determine cell viability, apoptosis, endoplasmic reticulum (ER) stress, and inflammatory.In vivo, male C57BL/6 mice were fed a 60% high-fat diet (HFD) for 12 w. Then the lard in HFD was partially replaced with fish oil (FO) and olive oil (OO) at low or high proportions of energy (5% or 20%) to observe the ameliorative effects of the UFA supplement.Results: All UFAs significantly improved PA-induced cell viability impairment in INS-1E cells, and their alleviation on PA induced apoptosis, ER stress and inflammation were confirmed. Particularly, OA had better effects than EPA, DHA, and AA on attenuating cellular ER stress. In vivo, the diets with a low proportion of UFAs (5% of energy) had limited effects on HFD induced metabolic disorder, except for a slight improved intraperitoneal glucose tolerance in obese mice. However, when fed diets containing a high proportion of UFAs (20% of energy), both the FO and OO groups exhibited substantially improved glucose and lipid metabolism. Unexpectedly, FO resulted in abnormal elevation of the liver function index aspartate aminotransferase (AST) in serum. Pathologically, OO attenuated HFD-induced compensatory hyperplasia of pancreatic islets, while this effect was not obvious in the FO group.Conclusions: Both MUFAs and PUFAs can effectively protect islet β cells from SFA-induced cellular lipotoxicity. In particular, both OA in vitro and OO in vivo showed superior activities on protecting islets function and enhance insulin sensitivity, suggesting that MUFAs might have greater potential for nutritional intervention on diabetes.